Study of the antimicrobial activity of new quinazoline derivatives against Staphylococcus aureus - M. A. Samotrueva; A. A. Starikova; A. A. Tsibizova; S. Yu. Kozlov; I. N. Tyurenkov; A. A. Ozerov (Сибирский научный медицинский журнал, 2025)
The aim of the study was to study the antimicrobial activity of new quinazoline derivatives against Staphylococcus aureus with the prediction of the structure-activity relationship.   Material and methods. Primary antimicrobial screening of new quinazoline derivatives was carried out using the serial dilution method. The number of colonies was counted using the BIOMIC V3 software and hardware complex (Giles Scientific, USA). For statistical processing of the study results, the StatTech program (Russia) was used using the parametric method with the definition of Student’s t-test with Bonferroni correction. Prediction of direct biological targets was carried out using the PASS software tool. Structural parameters and octanol/water partition coefficient (LogP) were determined using ProTox 3.0.   Results. The bacteriostatic effect of the substance VMA-23-10 against S. aureus was established in dilutions of 128, 64 and 32 μg/ml. It has been shown that VMA-23-10, distinguished by the presence of an isopropyl radical in the molecule, is characterized by greater lipophilicity. The mechanism of action of the substance VMA-23-10 was predicted.   Conclusions. The conducted study made it possible to identify the leading compound among the studied derivatives, which exhibits a bacteriostatic effect against S. aureus. The difference in lipophilicity between VMA-23-10 and other molecules studied probably determines their different ability to penetrate the cell membrane of the pathogen. The predicted probability of the effect of the compound VMA-23-10 on serine/threonine protein kinases suggests that it exhibits an antimicrobial effect due to disruption of peptidoglycan synthesis, as well as suppression of the process of biofilm formation.